R&D and aggregate fluctuations - Erhan Artuç; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2012)
Using US data for the period 1959-2007, we identify sectoral productivity shocks and capital investment-specific shocks by employing a Vector Autoregression whose shock structure is disciplined by a general equilibrium model. Controlling for real and nominal factors, we find that capital investment-specific shocks explain 70 percent of fluctuations of R&D investment while R&D technology shocks explain 30 percent of the variation of aggregate output net of R&D investment (i.e. the output of the non-R&D sector). Technology shocks jointly explain almost all the variation of output in the R&D sector and 78 percent of the variation of output in the non-R&D sector.
Keywords: C13; C32; C68; E32; O3; 330; Cycles; Productivity Shocks; Investment-specific Shocks; R&D; VAR; Forschung; Investition; Technischer Fortschritt; Nachhaltige Entwicklung; USA